ChemInform Abstract: Cube‐in‐Cube Hollow Cu9S5 Nanostructures with Enhanced Photocatalytic Activities in Solar H2 Evolution. Issue 3 (January 2015) - Xu, Miao; Wang, Min; Ye, Tiannan; Liang, Na; Jin, Lun; Zai, Jiantao; Qian, Xuefeng
Abstract The title nanostructures are hydrothermally prepared by dropwise addition of CS2 into a mixture of aqueous polyvinylpyrrolidone, CuSO4, NaOH, and ascorbic acid (autoclave, 120 °C, 12 h).